President's Message - Hollett, Sharon (Operating Room Nurses Association of Canada Journal, 2024)
Due to the timelines involved in preparing a journal of this type this President’s Message was written for you in September. September 11th to be exact. The internet has been filled with images of the devastation of 9/11 from twenty years ago. Many of us can remember exactly where we were that day. I was working in room eight, our plastics room. Our anaesthesiologist received a telephone call telling him about the first plane. There was disbelief and shock as we continued to hear the reports throughout the day from the staff room where the only television set was located. Our thoughts were with all New Yorkers that day. Our perioperative nursing colleagues were no doubt preparing for the influx of the injured.